Penerapan Pembelajaran Kooperatif Model Two Stay Two Stray untuk Meningkatkan Lima Unsur Pembelajaran Kooperatif dan Prestasi Belajar Siswa Kelas X MAN Salido - Huriati Huriati (Departement of Mathematics Education, 2023)
This study aims to find out how the application of the Two Stay Two Stray Cooperative Learning Model to Improve the Five Elements of Cooperative Learning and Student Achievement of class X MAN Salido. This research is a type of classroom action research (PTK) with a qualitative approach that displays everything that happens naturally, as it is without manipulation. The subjects of this study were 32 students of class X MAN Salido with heterogeneous levels of academic ability and ethnicity. Learning through the Two Stay Two Stray method can increase the activity and learning outcomes of class X MAN Salido. The results of the study showed that the results of observations of student activity in the first cycle were 70.60% of students in the active category then increased in the second cycle to 80.55% of active students. Classical completeness learning outcomes in the first cycle reached 67.74% and in the second cycle increased to 93.55%.